Stress as a Determinant: Exploring Predictors of Post-Covid-19 Pandemic Professional Quality of Life Among Nurses - Khairina, Ilfa; Maisa, Esthika Ariany; Rahman, Dally (GLOBAL HEALTH SCIENCE GROUP, 2024)
The Covid-19 Pandemic, spanning from 2020 to 2022, ushered in unprecedented challenges for the healthcare system, impacting nurses who played a pivotal role in the global and Indonesian responses. Nurses faced emotional exhaustion, diminished job satisfaction, and suboptimal working conditions, compounded by increased responsibilities and monotony in delivering healthcare services. Objective: This study aimed to identify predictive factors influencing the post-pandemic quality of life among nurses in Padang City hospitals. Utilizing purposive sampling, 88 nurses participated, providing data through a demographic questionnaire, Perceived Stress Scale, and Professional Quality of Life Scale (ProQoL-21). Nurses' quality of life (p-value = 0.000). Conversely, age, gender, tenure, experience in caring for Covid-19 patients, and career level exhibited no significant correlations. The findings underscore the importance of addressing stress as a determinant of nurses' well-being. Care managers at Padang City Hospital can leverage these insights to enhance nurses' quality of life, ultimately optimizing healthcare delivery to the community. This study offers valuable guidance for healthcare management, emphasizing the need to prioritize stress management interventions to bolster the overall effectiveness of nursing care.